Immune Checkpoint Inhibitor–Associated Tumor Lysis Syndrome: A Real-World Pharmacovigilance Study - Wang, Li; Li, Xiaolin; Zhao, Bin; Mei, Dan; Jiang, Jiandong; Duan, Jingli (Frontiers in Pharmacology, 2021)
Introduction: Immune checkpoint inhibitors (ICIs) have substantially improved the clinical outcomes of various malignancies. However, the adverse event of tumor lysis syndrome (TLS) has not been included in the National Comprehensive Cancer Network guidelines or drug inserts. In this study, we aimed to establish the relationship between ICI therapies and TLS events using data from a real-world pharmacovigilance database. Methods: The MedDRA terms of TLS and both generic and brand names of ICIs were retrieved from the FDA Adverse Event Reporting System. Four frequentist algorithms were employed to confirm the association between the TLS and the ICI regimens, involving anti-cytotoxic T lymphocyte antigen-4 (anti-CTLA-4), anti–programmed death receptor-1 (PD-1)/programmed cell death 1 ligand 1 (PD-L1), and anti-(CTLA-4 + PD-1). A descriptive and statistical analysis was performed according to the case information. Results: One hundred sixty-four TLS cases, where patients underwent anti-CTLA-4 (n = 14), anti-(PD-1)/(PD-L1) (n = 113), or anti-(CTLA-4 + PD-1) (n = 37) therapies, were collected between the first quarter of 2004 and the fourth quarter of 2020. The most coverage-reporting year, age-group, sex, reporter, region, country, and indication were 2020 (n = 62), 60–74 years (n = 65), males (n = 105), physician (n = 66), Asia (n = 80), Japan (n = 67), and lung and thymus malignancies (n = 40), respectively. The median TLS onset time associated with anti-CTLA-4, anti-(PD-1)/(PD-L1), and anti-(CTLA-4 + PD-1) therapies was 6 (IQR: 2–39.5), 9 (IQR: 2–40), and 20 (IQR: 7.5–37.75) days, respectively. Mortality distribution of 71 reported death outcomes among three groups was statistically significant. All four algorithm signal values of anti-(CTLA-4 + PD-1) were higher than those of anti-CTLA-4 and anti-(PD-1)/(PD-L1). Conclusion: Elderly male patients with lung and thymus malignancies are frequently predisposed to TLS. ICI therapies could induce TLS in both solid and hematological malignancies. The rapid onset time and poor outcomes of patients prompt caution from health-care professionals.